Searching for Ways to Improve Visiting Oral Health Care Services in Korea through Comparison with Japanese System in Long-Term Care Insurance - Sang-Hwan Oh; Rumi Nishimura; Soo-Jeong Hwang (The Korean Society of Dental Hygiene Science, 2023)
Background: Legal regulations and fees have been established in Korea to provide visiting oral health care services to individuals with long-term care insurance (LTCI). However, beneficiaries of this service are very limited. Therefore, to improve the Korean system we propose a comparative analysis with the Japanese system. Methods: This study is a descriptive analysis based on secondary data, such as statistics, laws, and service record forms from Korea and Japan. The most recent institutional documents were obtained through a Google search. The variables investigated were financial resources of LTCI, co-payment structure, monthly limit of LTCI benefits, care levels of LTCI, service providers, service costs, contents of service, and the number of cases of service. Results: In both Korea and Japan, LTCI is financed through a combination of taxes and insurance premiums. However, the monthly limit for receiving LTCI services in Japan is about 2.4 times higher than in Korea. Visiting medical and dental treatment is also possible in Japan. Furthermore, nursing staff can provide daily oral health care services according to dental hygienists' instruction unlike Korea. Oral health care services in Korea are focused on oral hygiene and prevention of oral diseases, while Japan additionally provides oral function screening, patient education for oral health management, and training for nursing staff to enhance oral function, eating, and swallowing of the patients. Conclusion: We concluded that the possibility of visiting dental treatment, differences in monthly limit of LTCI benefits, oral function assessment and guidance, as well as collaboration with other healthcare professionals contributed to the difference in the frequency of utilization of visiting oral health care services between Korea and Japan.